Inclusive Globalization and The Belt and Road Initiative - Xie, Jingyi (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2023)
The old economic globalization has come to a halt. Most scholars have considered the current model of economic globalization, and the new path of globalization is to inherit the parts of neoliberal economic globalization that benefit economic growth while reforming the parts that are insufficient. Many academics have backed China’s "Belt and Road" initiative (BRI) as a platform for jointly exploring a new type of globalization in this context. Based on a brief overview of the economic globalization development process, this article investigates how the BRI reflects the characteristics of inclusive globalization in its policies. Equal opportunity, balanced benefits, shared development, and openness are the four characteristics investigated. This article demonstrates, using qualitative methods and a literature review, that BRI has fulfilled all of these characteristics of inclusive globalization, with a wide range of programs carried out under the BRI scheme. In Exconclusion, BRI can be used as a "role model" for implementing inclusive globalization.